Developing Social Indicators - Duncan, Otis Dudley (1974)
Recent progress in developing social indicators is described in terms of six activities. In regard to social bookkeeping, we are expanding the number of domains covered by population surveys, and survey data are being more widely disseminated. In social accounting, demographic stock-flow schemes show promise of integrating systems of social statistics. Social science theories have provided models of achievement and other social processes. Social forecasting is potentially an important component of work on social indicators, but a new definition of the purpose of forecasting is needed. The practice of social reporting is best exemplified in the work of recent commissions. Social advising, while it draws upon social indicators, involves functions that cannot be performed by any system of indicators alone. The most worthy aspiration of the social indicators movement would be to contribute to the enlightenment of a changing society.